FRONTPAGE PROJECT: Symposium - Pericleous, Vicky (My University, 2024)
FRONTPAGE PROJECT - Exhibition | Symposium | Workshop, Department of Fine Arts, School of Fine and Applied Arts, CUT - Cyprus University of Technology, Limassol Municipal University Library, November 20 – 29, 2024 Group exhibition | symposium | workshop centered on the themes of "front page" and "headline news" in print and digital media. Participants include artists and cultural producers from the visual arts, from academic fields, and the media. The Department of Fine Arts at the School of Fine and Applied Arts of Cyprus University of Technology (CUT) develops and organises the second part of the international investigative project FRONTPAGE in collaboration with the European Communication Institute (ECI), in partnership with the Athenian Macedonian News Agency (AMNA) and the open visual arts group AxionArt and the collaboration of the Video Art Festival Miden (Mηδέν). It is supported by various academic institutions, including Donau-Universität Krems (DUK). In Cyprus, the research project is curated and organised by assistant professor and visual artist Vicky Pericleous and [Ρε:Re] Speculative Fine Art Practices Lab (CUT), which she develops and coordinates, visual artist Andreas Savva (special teaching staff), and curatorial assistant, Rebecca Taki, student of the MA History and Theory of Art, (CUT), with the support and involvement of the Department of Fine Arts (CUT). The FRONTPAGE project will unfold through a public symposium featuring esteemed academic speakers addressing topics relevant to the project, alongside the international FRONTPAGE exhibition at Limassol Municipal University Library, and a visual art workshop that engages academics from various fields and students from the Department of Fine Arts at CUT. The outcomes of the workshop will be presented in 2025 in Athens in an expanded exhibition featuring student work from the Athens and Thessaloniki Schools of Fine Arts, the University of West Attica (ΠΑ.Δ.Α.), the Department of Digital and Performing Arts of the University of Peloponnese, the Ionian University, as well as contributions from established artists. *Symposium: Wednesday, November 20, 2024, 10:30 AM - 2:30 PM, Limassol Municipal University Library. Invited Speakers: Maria Efstathiou, Curator, General Director of the Center for Visual Arts and Research (CVAR), Efi Kyprianidou, Assistant Professor, Department of Fine Arts (CUT), Eva Marangaki, Visual Artist/Concept/Curator (AXIONART), George Markou, Assistant Professor, Department of Fine Arts (CUT), Marios Nottas, Director of the European Communication Institute, ECI, Andreas Panayiotou, Associate Professor, Department of Phycology and Social Sciences, (Frederick University), Aspasia Papadima, Associate Professor, Department of Multimedia and Graphic Arts (CUT), Vasiliki (Vicky) Triga, Associate Professor, Department of Communication and Internet Studies (CUT), Julia Sysalova, Curator, Art Critic, and Communication in Art Educator. - Symposium Organizer | Coordinator: Vicky Pericleous, Assistant Professor, Department of Fine Arts, School of Fine & Applied Arts, Cyprus University of Technology
Keywords: Arts; Symposium; FRONTPAGE; News; Media Communication; Aesthetics; Social-Political Constructs & Representations in Arts & Communication